ALT CHANGES AND ADVERSE EVENTS OF TELBIVUDINE IN HEPATITIS-B PATIENTS-AN EXPERIENCE OF 11 PATIENTS - Ali, Zeeshan; Maheshwary, Neeta; Zara, Uffaq; Ahson, Siddiqi; Khan, Muhammad Athar (Journal of Ayub Medical College Abbottabad, 2015)
Hepatitis-B virus (HBV) infection is a major global health problem. Of the two billion people who have been infected, more than 350 million have chronic hepatitis. It is estimated that 235,000-328,000 people die annually due to liver cirrhosis and hepatocellular carcinoma, we assessed the short term outcomes of treatment with telbivudine in 11 adults aged 14-41 years with HBeAg-positive or HBeAg-negative chronic hepatitis-B (CHB). Treatment of chronic hepatitis-B patients with telbivudine shows 43.1% reduction in serum ALT with no significant adverse effects. Keywords: Telbivudine, Hepatitis-B Virus, Hepatocellular Carcinoma, HBeAg